Preliminary Study on the Kinetics and Mechanism of the Oxidation of Naphthol Green B by Dichromate Ion in Aqueous Hydrochloric Acid Medium - Bako Myek; Sulaiman O. Idris; Johnson F. Iyun (Aceh International Journal of Science and Technology, 2014)
Abstract - The kinetics of the oxidation of naphthol green B (NGB3-) by Cr2O7 2- has been studied in aqueous hydrochloric acid medium at an ionic strength, I = 0.50 mol dm-3 (NaCl), H+ =1.0  10-4 mol dm-3 (HCl) and T = 25  1C. The redox reaction displayed a stoichiometry of 1:1 and obeys the rate law: -dNGB3-/dt = k2NGB3-]Cr2O7 2- . The second order rate constant increases with increase in acid concentration and in the ionic strength of reaction medium. The rates of reaction displayed a positive salt effect. Addition of acrylonitrile to a partially reacted mixture in the presence of excess methanol did not lead to gel formation. Added cations and anions inhibited the naphthol green B - Cr2O7 2- reaction. Results of the Michaelis – Menten plot gave no evidence of intermediate complex formation during the course of the reaction. Based on the results obtained, the reaction is believed to proceed through the outersphere mechanistic pathway.Keywords: Intermediate; Redox; Pseudo-octahedral; Michaelis – Menton; Outersphere